PENGARUH KUALITAS LAYANAN DAN CITRA PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN CONATO BAKERY GAJAH MADA JEMBER - Dindin Aldila Kustantia; Nurul Qomariah; Akhmad Fahrur Rozi (Jurnal Manajemen dan Bisnis, 2021)
The current economic development is increasingly leading to fierce competition, especially for similar companies or businesses. This makes the competition between companies even tighter in the struggle for market share. Every company wants to be successful in running its business. One company that is experiencing intense competition with other similar companies is a bakery company. The purpose of this study is to determine and analyze the effect of service quality and product image on purchasing decisions partially. The population in this study were consumers of "Conato Bakery Gajah Mada Jember". This research includes quantitative research using survey methods. The type of data used is primary data obtained from distributing questionnaires using purposive sampling method and the number of samples obtained is 100 respondents. This study uses multiple linear regression. The results showed that the variable service quality and product image had an influence on the purchase decision of the bread "Conato Bakery Gajah Mada Jember". Each variable has a positive and significant effect on purchasing decisions.